(untitled) (Journal of Engineering, 2025)
When selecting a material for product design, the focus is on its mechanical properties, a standard requirement in most applications. This paper’s research aimed to determine if better calibration of polymethyl methacrylate (PMMA) material samples welded with laser spot welding could be achieved by verifying joint strength performance and modulus of elasticity. Tensile tests were conducted using a universal testing machine with a 100 kN load capacity. Parameters studied included laser power, welding velocity, laser focus diameter, and spot geometric size. An orthogonal L9 array with three levels was used. Multi-objective optimization techniques TOPSIS-Quality Loss Function were used, and the results were compared. It was discovered that the first experiment among the nine experiments had the best multi-quality features with the following parameters: laser power of 10 W, welding velocity of 10 mm/s, laser focus diameter of 0.002 mm, and spot geometric size of 4 mm. It was observed that the geometric spot design is the most effective parameter for quality at a small size. It was proven that the smaller size of the geometric spot increases the strength and stiffness of the welded product.